Utilizing data mining techniques to analyze payment order rejections in the state treasury office - Alhadi, Iqbal; Prakoso, Bimantara Gusti Aji (Program Studi Akuntansi IKOPIN, 2025)
One of the challenges in budget implementation was the rejection of Payment Orders (SPM), which led to delays in bill payments and a decline in the quality of budget execution. To analyze SPM rejections, data mining techniques utilizing a decision tree model were applied to 15,030 data records obtained from State Treasury Office (KPPN) Palu, covering the 2019 fiscal year. The analysis revealed that SPM-Contractual, SPM-Others, Non-Salary, and PPNPN were the most frequently rejected Payment Orders. Furthermore, Payment Orders associated with a relatively large budget ceiling had a higher probability of rejection. The findings of this study can serve as a reference for KPPN Palu in developing technical guidance to minimize administrative errors based on the analyzed attributes.